1984
DOI: 10.1152/ajpendo.1984.247.5.e625
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an intestinal mechanism in hypercalciuria of spontaneously hypertensive rats

Abstract: To define the mechanism for the hypercalciuria in spontaneously hypertensive rats (SHR), Ca clearance was evaluated in fasted 23-wk-old SHR and normotensive Wistar Kyoto (WKy) controls. There was no exaggerated calciuria before or after parathyroidectomy. Ca balance was therefore measured in the nonfasted animals, which revealed hyperabsorption in SHR of both sexes with increments 10-fold that of Ca excretion, supporting the primacy of intestinal hyperabsorption. In situ duodenal Ca uptake was also increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
52
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 7 publications
8
52
1
Order By: Relevance
“…Previous studies at 12 wk of age do not support the role of changes in vitamin D metabolism or sensitivity, since serum 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] levels were not measurably different (8), and the acute response to exogenous 1,25(OH)2D3 was blunted in the everted gut sac or perfused duodenum ofSHR (9). In the former study, serum concentrations of 1,25(OH)2D3 in prehypertensive SHR were however not evaluated (8).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies at 12 wk of age do not support the role of changes in vitamin D metabolism or sensitivity, since serum 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] levels were not measurably different (8), and the acute response to exogenous 1,25(OH)2D3 was blunted in the everted gut sac or perfused duodenum ofSHR (9). In the former study, serum concentrations of 1,25(OH)2D3 in prehypertensive SHR were however not evaluated (8).…”
Section: Introductionmentioning
confidence: 92%
“…Previous balance studies by our laboratory in the adult spontaneously hypertensive rat (SHR)' documented an increased net Ca absorption (1). These changes are associated with enhanced duodenal Ca uptake in situ and with absorptive hypercalciuria (1).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Calcium metabolism in SHR has been shown by several studies to be abnormal. These abnormalities include reduced serum ionized calcium, increased serum parathormone levels, hypercalciuria, and abnormal vitamin D metabolism (9)(10)(11)(12)(13)(14)(15)(16). Studies on calcium transport using in vivo and in vitro techniques, in general, have shown decreased calcium uptake by the small intestine of the SHR when compared with WKY (12,15,16,17,18).…”
mentioning
confidence: 99%